1990
DOI: 10.1016/0014-5793(90)80298-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of non‐phenolic substrates

Abstract: In the presence of substrates such as Remazol Blue and 2,2'-azlnobls(3-ethylbenzthiazoline-6-sulphonate) (ABTS), laccases Cor~olus / Trumeterj vers~olor can also oxidize non-phenolic lignm model compounds Veratryl alcohol (I) and 1-(3,4-dlmethoxyphenyl)-2-(2-methoxyphenoxy)-propane-1.3-dtol (III) were oxtdized by lactase and medrator to give the a-carbonyl derivativesThe p-1 hgnin model dtmer, 1-(3,4-dimethoxyphenyl)-2-phenoxy-ethane-I ,2-dtol (II) was cleaved by lactase in the presence of ABTS to give veratra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
286
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,200 publications
(295 citation statements)
references
References 12 publications
6
286
0
3
Order By: Relevance
“…In fact, it has been reported that the radical mediator ABTS is able to bring about the oxidation of non-phenolic systems characterized by a redox potential higher than laccase such as veratryl alcohol or non-phenolic b-O-4 model compounds. 3 In contrast, recent ®ndings have also shown that the reactivity of benzylic alcohols in the presence of the laccase-mediator system depends on the substitution pattern on the aromatic ring. 18,23 In particular, 2,6-disubstituted benzylic alcohols were found to be unreactive with the laccase-mediator system.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, it has been reported that the radical mediator ABTS is able to bring about the oxidation of non-phenolic systems characterized by a redox potential higher than laccase such as veratryl alcohol or non-phenolic b-O-4 model compounds. 3 In contrast, recent ®ndings have also shown that the reactivity of benzylic alcohols in the presence of the laccase-mediator system depends on the substitution pattern on the aromatic ring. 18,23 In particular, 2,6-disubstituted benzylic alcohols were found to be unreactive with the laccase-mediator system.…”
Section: Discussionmentioning
confidence: 97%
“…2 In order to elucidate the deligni®cation mechanism catalyzed by laccase, several studies have been carried out on both phenolic and non-phenolic monomeric, arylglycerol b-O-4 and b-1 ether lignin model compounds. 3±5 The use of radical mediators has become of interest since the early report that non-phenolic lignin model compounds, unreactive towards laccase alone, could be oxidized in the presence of laccase and ABTS, 3 and that kraft pulp could be deligni®ed. Since then, 1-hydroxybenzotriazole was found to mediate pulp deligni®cation in the presence of laccase.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, laccase was not considered as an enzyme suitable for the complete oxidation of lignin because of the low redox potential of the enzyme that did not allow for oxidation of non-phenolic lignin structures. However, Bourbonnais and Paice [8] showed that the artificial laccase substrate ABTS could act as a redox mediator which enabled laccase to oxi-*Corresponding author. Fax: (1) (706) 542-2222.…”
Section: Introductionmentioning
confidence: 99%
“…The ligninolytic potential of fungal laccases was evaluated rarely because laccase does not oxidize non-phenolic structures which are predominant in lignin. However, it was found that the Coriolus versicolor laccase oxidized non-phenolic compounds in the presence of aromatic electron-transfer mediators [4].…”
Section: Introductionmentioning
confidence: 99%